D-dopachrome tautomerase predicts outcome but not the development of acute kidney injury after orthotopic liver transplantation. Issue 4 (April 2019) - Baron-Stefaniak, Joanna; Schiefer, Judith; Lichtenegger, Paul; Miller, Edmund J.; Berlakovich, Gabriela A.; Faybik, Peter; Baron, David M.
Abstract: Background: Elevated concentrations of D-dopachrome tautomerase (D-DT) were associated with adverse outcome in various clinical settings. However, no study assessed D-DT concentrations in patients requiring orthotopic liver transplantation (OLT). The aim of this observational study was to measure serum D-DT concentrations in patients undergoing OLT and associate D-DT with survival and acute kidney injury (AKI). Methods: Forty-seven adults with end-stage liver disease undergoing OLT were included. Areas under the receiver operating curves (AUC) were calculated to assess predictive values of D-DT for outcome and AKI after OLT. Survival was analyzed by Kaplan–Meier curves. Results: Serum D-DT concentrations were greater in non-survivors than in survivors prior to OLT (86 [50–117] vs. 53 [31–71] ng/ml, P = 0.008), and on day 1 (357 [238–724] vs. 189 [135–309] ng/ml, P = 0.001) and day 2 (210 [142–471] vs. 159 [120–204] ng/ml, P = 0.004) following OLT. Serum D-DT concentrations predicted lethal outcome when measured preoperatively (AUC = 0.75, P = 0.017) and on postoperative day 1 (AUC = 0.75, P = 0.015). One-year survival of patients with preoperative D-DT concentrations >85 ng/ml was 50%, whereas that of patients with preoperative D-DT concentrations <85 ng/ml was 83% (Chi 2  = 5.83, P = 0.016). In contrast, D-DT was not associated with AKI after OLT. Conclusion: In patients undergoing OLT, serum D-DT might predict outcome after OLT.